Development of Internet of Things-Related Monitoring Policies. Issue 4 (2nd October 2017) - Kaupins, Gundars; Stephens, Janet
ABSTRACT: The Internet of Things (IoT) is a loosely defined term describing internet-connected sensors that among other capabilities enable companies to monitor individuals. New privacy-related challenges can arise when sensors communicate with each other. These challenges call for changes to corporate privacy policies to incorporate potential IoT issues and guidance. This research investigates existing privacy policies and IoT-related research to provide IoT privacy policy recommendations. Privacy policy questions include: Who or what is notified of monitoring? When and where should there be expectations of privacy? Why and how is user data collected and how should monitoring problems be communicated? The analysis concludes with IoT-related privacy policy recommendations.